Variasi Komposisi Eluen pada Isolasi Steroid dan Triterpenoid Alga Merah Eucheuma cottonii dengan Kromatografi Kolom Basah - Armeida Dwi Ridhowati Madjid; Dwi Anik Rahmawati; Ahmad Ghanaim Fasya (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2020)
Steroid and triterpenoid compounds in petroleum ether fractions of red algae Eucheuma cottonii were isolated by slurry column chromatography. Isolation was started with maceration extraction using methanol solvent. The methanol extract was hydrolyzed with HCl 2 N and partitioned using petroleum ether solvent. The presence of steroid and triterpenoid was determined by phytochemical test using Lieberman Burchard reagent. Petroleum ether fraction was separated by slurry column chromatography with the variation of eluent composition n-hexane: ethyl acetate 16:4; 17:3; 18:2. The isolates were monitored by analytical thin-layer chromatography (TLC) and the best result was identified using FTIR. Percent yields of methanol extract and petroleum ether fraction were 11.866% and 8.03%, respectively. The optimum eluent composition in column chromatography for separation was n-hexane : ethyl acetate (18:2) obtained 2 steroid and 3 triterpenoid fractions. FTIR analysis gives information about functional groups of –OH, C=C, C-O, CH2, -C(CH3)2forsteroids and functional groups of –OH, C=O, C=C, CH2, -C(CH3)2 for triterpenoid.Keywords: Eucheuma cottonii, column chromatography, steroid, triterpenoid, variation of eluent composition Senyawa steroid dan triterpenoid dalam fraksi petroleum eter alga merah Eucheuma cottonii telah diisolasi menggunakan kromatografi kolom basah. Isolasi dilakukan dengan cara ekstraksi maserasi menggunakan pelarut metanol. Ekstrak pekat metanol dihidrolisis dengan HCl 2 N dan dipartisi menggunakan pelarut petroleum eter. Senyawa steroid dan triterpenoid diuji fitokimia menggunakan reagen Lieberman Burchard. Fraksi petroleum eter dipisahkan menggunakan kromatografi kolom basah variasi komposisi eluen n-heksana:etil asetat dengan perbandingan 16:4; 17:3; dan 18:2. Hasil isolasi dimonitoring menggunakan kromatografi lapis tipis (KLT) analitik. Hasil monitoring yang terbaik diidentifikasi gugus fungsinya menggunakan FTIR. Hasil penelitian menunjukkan rendemen ekstrak metanol dan fraksi petroleum eter masing-masing sebesar 11,866% dan 8,03%. Pemisahan kolom dengan variasi komposisi eluen n-heksana:etil asetat terbaik adalah 18:2 dengan diperoleh 2 kelompok fraksi steroid dan 3 kelompok fraksi triterpenoid. Hasil analisis FTIR pada isolat steroid memberikan informasi gugus –OH, C=C, C-O, CH2, -C(CH3)2, sedangkan isolat triterpenoid memberikan informasi gugus –OH, C=O, C=C, CH2,-C(CH3)2. Gugus gem dimetil (-C(CH3)2)merupakan ciri khas rantai samping steroid ataupun triterpenoid.Kata kunci: Eucheuma cottonii, kromatografi kolom, steroid, triterpenoid, variasi komposisi eluen